Pro/ENGINEER wildfire 4.0 instructor - Kelley, David S. (McGraw-Hill Higher Education, 2009)
Contents: Introduction to parametric design; Pro/Engineer's user interface; Constraint-based sketching; Extruding, modifying, and redefining features; Feature construction tools; Feature manipulation tools; Sections and advnaced drawing views...